THU0143 Pharmacokinetics, Bioavailability and Safety of A Modified Release Once Daily Formulation of Tofacitinib in Healthy Volunteers. (10th June 2014) - Lamba, M.; Wang, R.; Fletcher, T.; Alvey, C.; Hazra, A.; Kushner, J.; Larmann, J.; Stock, T.
Abstract : Background: Tofacitinib is a novel, oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). The efficacy and safety of an immediate-release (IR) formulation of tofacitinib, dosed twice daily (BID), has been assessed in patients with active moderate to severe RA. To facilitate once daily (QD) dosing, a novel modified-release (MR) formulation has been designed to achieve comparability of key systemic exposure parameters. Objectives: To compare the extent of exposure between a single dose of tofacitinib MR 11 mg vs an IR 2x5 mg dose in healthy volunteers (HV). Methods: This was a randomised, open label, 2-way cross-over study conducted in 26 HV. Following an overnight fast, HV were randomised to receive either a single dose of MR 11 mg (MR; test) or IR 2 x 5 mg (IR; reference). Treatments were separated by a 72-hour (h) washout. Pharmacokinetic (PK) parameters were calculated using non-compartmental analyses. The primary endpoint was extent of tofacitinib exposure, measured as area under the concentration-time curve from time zero extrapolated to infinite time (AUCinf ). A mixed-effects model was used to generate adjusted geometric mean ratios (MR/IR) and 90% confidence intervals (CIs). The steady-state (SS) profiles of tofacitinib MR and IR were predicted using single-dose data from this study. Results: All 26 HV completed the study and were included in the analyses. The study population had a mean age of 33.6 years, a mean body weight of 77.5 kg, and was 19% female. For the MR and IR formulations, geometric mean AUCinf (ng*h/mL) was 297.5 and 286.3, respectively, resulting in an MR/IR ratio of 103.91% (90% CI: 100.49%, 107.45%). Maximum plasma concentration (Cmax ; ng/mL) adjusted for formulation was 40.75 and 44.10 for MR and IR, respectively, resulting in an MR/IR ratio of 92.40% (90% CI: 84.99%, 100.45%). For both parameters, 90% CI values were wholly contained within the 80–125% range of bioequivalence. Mean terminal half-life was 5.71 h and 3.41 h for MR and IR formulations, respectively. The most common adverse events (AEs) were nausea, abdominal pain, back pain and headache. The incidence of AEs was similar between treatment groups and no serious AEs were reported. Predictions following SS dosing indicate similar time above JAK1/3 half maximal inhibitory concentration signalling thresholds and similar AUC, peak concentration and minimum concentration values between MR and IR formulations. Conclusions: This study demonstrates the single dose equivalence of AUCinf and Cmax of the MR and IR formulations of tofacitinib. Single doses of both formulations were well tolerated. This novel MR formulation of tofacitinib facilitates an opportunity to enable QD dosing, while maintaining systemic drug concentrations similar to the IR formulation (administered BID). Multiple-dose studies will be conducted to confirm the predictions of the SS PK profile and demonstrate equivalence between formulations following SS dosing. Acknowledgements: This study was sponsored by Pfizer Inc. Pfizer personnel were involved in protocol development and data analysis. Editorial support was provided by Claire Cridland of CMC and funded by Pfizer Inc. Disclosure of Interest: : M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Fletcher Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Alvey Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Hazra Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Kushner Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Larmann Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Stock Shareholder of: Pfizer Inc, Employee of: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.1521